2016
DOI: 10.1186/s12889-016-2763-0
|View full text |Cite
|
Sign up to set email alerts
|

Variations in schools’ commitment to health and implementation of health improvement activities: a cross-sectional study of secondary schools in Wales

Abstract: BackgroundInterventions to improve young people’s health are most commonly delivered via schools. While young people attending the lowest socioeconomic status (SES) schools report poorer health profiles, no previous studies have examined whether there is an ‘inverse care law’ in school health improvement activity (i.e., whether schools in more affluent areas deliver more health improvement). Nor have other factors that may explain variations, such as leadership of health improvement activities, been examined a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 32 publications
1
16
0
Order By: Relevance
“…The finding that the least affluent school had the most comprehensive provision of support staff dedicated to well-being is consistent with previous literature, where a higher volume of health improvement activity has been found to be implemented in more deprived schools (Moore, Littlecott, Fletcher, Hewitt, & Murphy, 2016). However, this may lead to an oversight of the more deprived students who are attending more affluent schools who report poorer relationships with school staff (Moore et al, 2017).…”
Section: Discussionsupporting
confidence: 90%
“…The finding that the least affluent school had the most comprehensive provision of support staff dedicated to well-being is consistent with previous literature, where a higher volume of health improvement activity has been found to be implemented in more deprived schools (Moore, Littlecott, Fletcher, Hewitt, & Murphy, 2016). However, this may lead to an oversight of the more deprived students who are attending more affluent schools who report poorer relationships with school staff (Moore et al, 2017).…”
Section: Discussionsupporting
confidence: 90%
“…Schools with large student enrolment were more likely to be ''involved'' in knowledge brokering, consistent with findings that large schools are more committed to improving student health. 26 Larger schools may have more staff and resources to allocate toward student health compared to smaller schools.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, in school health research, developing and evaluating knowledge exchange strategies has been identified as a priority ; while initiatives are beginning to emerge, few evaluations have been published . However, 3 strategies have been recommended for youth health research: using research summaries (eg, reports, websites, newsletters) to spark conversations with knowledge users; building research‐practice‐policy partnerships; and adapting initiatives to meet specific stakeholder needs .…”
mentioning
confidence: 99%
“…Wales is one of 43 countries participating in the HBSC study internationally (Roberts et al ., ). In Wales, schools were also asked to complete questionnaires on the school environment and school health‐improvement actions (Moore et al ., ). Maintained and independent secondary schools in Wales were stratified by local authority and eligibility for free school meals, then selected using probability proportionate to size (and with an element of disproportionate stratification to allow analysis at Local Health Board level).…”
Section: Methodsmentioning
confidence: 97%